The Relationship Between Long-Suffering From Hypertension With The Level Of Anxiety In Elderly People With Hypertension At The Community Health Center Aceh Besar Regency, Indonesia - Muhammad Reza Rizki; Ellyza Fazlylawati; Reca Melati Phonna; Nabella; Arza Rufli (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg so it is often referred to as the silent killer because it does not show significant symptoms. The purpose of this study is to find out if there is a correlation between the length of suffering from hypertension and the level of anxiety of hypertension patients. The type of research used was a quantitative study on 58 respondents at the Community Health Center Aceh Besar Regency using a cross sectional study design with a sampling technique, namely convenience sampling. Data collection used the Hamilton Anxiety Rating Scale (HARS) questionnaire. The results obtained were that most of the patients with moderate hypertension with a BP of 160-180 mmHg were 28 respondents, 24 respondents had hypertension > 11 years, and 31 respondents had mild anxiety levels. The chi-square value between the length of time suffering from hypertension and the level of anxiety was p = 0.000. The conclusion of this study is that there is a relationship between the length of suffering from hypertension and the level of anxiety in the elderly. Keywords: Hypertension, Suffering from Hypertension, Anxiety.